(untitled) (Nexo Revista Científica, 2022)
In Nicaragua, studies of the western Malacofauna are relatively few, mainly for the Gastropoda subclass, having as the only references within the country studies carried out by MARENA, COMAP, USAID and FUNCOD in 2002, in which they identified about 106 species among flora and fauna, in which some bivalves are mentioned, on the other hand Santana Aguilar in 2006, identified 70 species of bivalves and 92 gastropods in the Cosigüina Natural Reserve, last but not least the books compiled by López and Urcuyo in 2008 , who make a record of the main characteristics of both subclasses, dividing the information into two volumes, one for each one, giving a photographic record at the end of each taking of the most common bivalve and gastropod species in the Pacific. However, these studies do not take a specific record of the coastal part of León, which presents a diversity of species of both subclasses and that are of great commercial interest for the community, since it is their source of economic income, therefore, The initiative arises to carry out this study on Santa Lucia Island, which is considered a buffer zone of the Juan Venado Nature Reserve, sharing species of both flora and fauna. The study was carried out in the months of September to November, after the end of the closed period of the Bivalvia subclass, taking samplings every 20 days, taking as a reference the northeast coastline of Santa Lucia Island, the coves of "El Rosario" and “El Gancho” (which are characterized by presenting the largest bivalve station and some gastropods, according to locals), a total of 360 specimens were captured, of which the presence of 19 species was identified in sizes from 1 centimeter to 22.9 centimeters, predominating in the case of the bivalves the genus Anadara sp., Of the subclass of the gastropods, the species of Rhinocoryne homboltdti, followed by Cerithidae sp., And Ilichione subrugosa, with the coastal zone presenting the greatest diversity of species of the gastropod subclass In comparison to the coves, however, the coves presented a greater dominance of species of the Bivalvia subclass.